Challenges associated with metal chelation therapy in alzheimer's disease - Hegde, Muralidhar L.; Bharathi, P.; Suram, Anitha; Venugopal, Chitra; Jagannathan, Ramya; Poddar, Pankaj; Srinivas, Pullabhatla; Sambamurti, Kumar; Rao, Kosagisharaf Jagannatha; Scancar, Janez; Messori, Luigi; Zecca, Luigi; et al. (Journal of Alzheimers Disease, 2009)
A close association between brain metal dishomeostasis and the onset and/or progression of Alzheimer's disease ( AD) has been clearly established in a number of studies, although the underlying biochemical mechanisms remain obscure. This observation renders chelation therapy an attractive pharmacological option for the treatment of this disease. However, a number of requirements must be fulfilled in order to adapt chelation therapy to AD so that the term ``metal targeted strategies'' seems now more appropriate. Indeed, brain metal redistribution rather than brain metal scavenging and removal is the major goal of this type of intervention. The most recent developments in metal targeted strategies for AD will be discussed using, as useful examples, clioquinol, curcumin, and epigallocatechin, and the future perspectives will also be outlined.
Keywords: Alzheimer's disease; clioquinol; cuprizone; metal dishomeostasis; metal ions; nanomedicine; Parkinson's disease; polyphenols

Interaction of alpha-mannosidase from aspergillus fischeri with glycosidase inhibitors, metal ions and group specific reagents - Shashidhara, K. S.; Gaikwad, S. M.; Khan, Mohammad Islam; Bharadwaj, Kishor Chandra; Pandey, G. (Research Journal of Biotechnology, 2009)
As an initial step towards using alpha-mannosidase as a target against anticancer drugs, inhibition studies of a model enzyme, class II alpha-mannosidase from Aspergillus fischeri in presence of polyhydroxy piperidine derived glycosidase inhibitors, metal ions and amino acid specific reagents were carried out to reveal the sensitivity of the enzyme. Three of the derivatives (Compound 20, 32 and 39)(11) showed competitive inhibition (K(i) =45, 48 and 235 mu M) and the binding of the inhibitors to the enzyme was entropically driven. Among the metal ions checked, Cu(++) (K(i) = 21nm) and Se(++) ions (K(i) = 32 mu M) showed noncompetitive and Co(++) (K(i) = 1.195 mM) showed competitive inhibition of the enzyme activity with insignificant change in the secondary structure of the protein. The above studies exhibit the Potential of the enzyme in studying anticancer drugs. Treatment of the enzyme with group specific reagents showed the presence of carboxylate, Arg and Cys at the active site. Substrate protection studies and kinetics of the modified enzyme confirmed the above results. Trp and His at the active site were observed to be in proximity.
Keywords: active-site; alpha-Mannosidase; Chemical modification; Glycosidase inhibitors; metal ions

Behavior of the transport and separation of lanthanum, yttrium and lutetium metal ions through a celluose fiber supported solid membrane - Gaikwad, Abaji G. (Macedonian Journal of Chemistry and Chemical Engineering, 2012)
A newly designed membrane cell was used to study the behavior of the transport and separation of lanthanum, yttrium and lutetium metal ions using a cellulose fiber supported solid membrane. The cellulose fiber membrane was prepared by the chemical modification of cellulose fiber using an esterification reaction with citric acid. Different experimental variables were investigated, such as time, membrane size, stirring of the source and receiving phases and the pH of the source phase. The use of different stripping agents in the receiving phase was explored, including nitric acid, hydrochloric acid, sodium nitrate, ammonium thiocyanate, D(2)EHPA, TBP, Aliquat-336, tartaric acid, EDTA and organic solvents. Pre-concentration of lanthanum, yttrium and lutetium metal ions from dilute solutions was carried out.
Keywords: binary mixture; cellulose fiber membrane; Citric acid; complexing reagent; Lanthanum; lutetium; metal ions; Separation; transport studies; yttrium